Strategi Pemberdayaan Perempuan di Desa Panggak Darat Kecamatan Lingga Kabupaten Lingga - Hidayah, Nur; Pangestoeti, Wahyu; Safitri, Dian Prima (Jurnal Ilmu Administrasi Negara (JUAN), 2014)
Program Pemberdayaan Perempuan (Women Empowerment Program) in Panggak Darat Village is oneof the women empowerment program organized by the local government through Badan PemberdayaanPerempuan, Perlindungan Anak, dan Keluarga Berencana (BP3AKB) Lingga regency to empowerwomen to be more empowered, by providing direct grants to the village which wa s then submitted totraining group women empowerment. With this program are expected to be more independent women.The Program is training activities such as weaving and sewing. The problem raised are (1) HowWomen Empowerment in Panggak Darat Village of Lingga District, (2) What strategy is used in theempowerment of women, (3) What are the enabling and inhibiting factors in the empowerment ofwomen. This research aims to determine the strategy of empowerment of women in Panggak DaratVillage through weaving and sewing training, as well as to determine the significance of this training.This study used a qualitative research approach, the type of research is descriptive. Subjects were headof women empowerment, training members, and the community including the village chief andchairman of the Trustees of Family Welfare. The data collection used were observation, interviews, anddocumentation. The fact in the location that women empowerment focuses was the Resource-BasedView (RBV), which focuses on human resources and natural resources in a region. While the strategy ofusing cedar mezzo-based strategies, namely strategies undertaken over several groups, such as weavingand sewing training groups, each group consisting of two groups of training. In weaving training, aftersome of the group members follow the development of creativity training, members of the group formedtwo groups worked together to weave and between groups. As for sewing training, conducted bypresenting a coach to teach you about how to sew a good clothes. The benefits obtained after training isempowering members acquire knowledge and skills that can then be developed to open their ownbusiness and can fulfill necesstityt.